MODEL SEL SIMULASI SELF-ASSEMBLED MONOLAYER REVERSIBEL - Saputri, Wahyu Dita (Jurnal Ilmu Kimia Universitas Brawijaya, 2015)
A simple model of simulation cell of self-assembled monolayer (SAM) with atomistic description was constructed for molecular simulation method. The SAM consists of protonated amine-alkanethiol immobiled on copper (Cu) as supporting surface. A molecular dynamics simulation was perfoemed using the constructed cell. The results showed that the simulation was stable and can be used to decribe the reversibility of SAM conformation.